The impact of patient- and family-centered care interventions on intensive care unit outcomes: a meta-analysis of randomized controlled trials - Yangjin LV; Peng Li; Ronghui Li; Ting Zhang; Kaifang Cai (Brazilian Journal of Anesthesiology)
Background: Patient and Family-Centered Care (PFCC) interventions are increasingly recognized as a viable approach to address various mental health issues among patients in Intensive Care Units (ICUs). Therefore, this review aims to estimate the effect of Patient and Family-Centered Care Interventions on specific outcomes in adult patients admitted to Intensive Care Units (ICUs). Methods: We systematically searched four major databases for parallel arm Randomized Controlled Trials (RCTs). The PRISMA framework was used to report our review. We included studies involving adult patients (> 18-years) admitted to ICUs and examined the effects of any type of Patient and Family-Centered Care intervention (PFCC) on outcomes such as depression, anxiety, delirium, and length of hospital stay. Data extraction was performed independently by two authors in Medline, Google Scholar, and ScienceDirect, from inception to July 2024. Random effects model was used to pool the data. Results: A total of 11 studies were included in our systematic review and meta-analysis, with a combined sample size of 3352 patients (PFCC group, n = 1681; usual care group, n = 1671). A random-effects model revealed a significant reduction in delirium prevalence in the PFCC group, with a pooled Risk Ratio (RR) of 0.54 (95% CI 0.36 to 0.81). However, no statistical significance was found for other outcomes such as depression, length of ICU stay, and anxiety. It is important to note that all the included studies were assessed to have either a high or unclear risk of bias. Conclusion: PFCC interventions may significantly reduce delirium rates among ICU patients; however, their effects on other outcomes, such as depression, anxiety, and length of stay, were not statistically significant.